La mort de Papa Alexandre VI, segons un poema anònim italià de 1504. - BENAVENT, JÚLIA (Scripta, 2017)
A poem in octaves about the death of Alexandre VI, unpublished and anonymous, printed in Italy, provides new data on the literature against the Borja family. In this instance, the poem portrays Alexandre VI as a necromancer who cannot see the announcement of his own death.